The power of provenance in the records continuum - Hurley, Chris; McKemmish, Sue; Reed, Barbara; Timbery, Narissa (Archival science, 2024)
This paper explores the meaning of provenance in its broader social and organisational context, ambience, through a records continuum lens, bringing a reflexive and critical perspective to records continuum thinking over the past 30 or so years. It begins by introducing key recordkeeping concepts and goes on to explore records continuum theory and the records continuum model, a four-dimensional map of the recordkeeping and archival contexts of creation, capture, organisation and pluralisation. Continuum principles of provenance and ambience are situated in the model. An analysis of how provenance is currently narrowly applied in practice leads into an exploration of the power of ambience and provenance in the continuum. The following sections on Participatory Rights in Childhood Recordkeeping in Out of Home Care in Australia and Living Archives on Country illustrate how these concepts, together with those of multiple, simultaneous and parallel provenance, can be powerful tools in transforming the subjects of records into active recordkeeping agents. The illustrative examples relate to pioneering research on co-designing extensive suites of rights for co-creators of records who were previously relegated to the status of subjects of the record, and Indigenous archival sovereignty. They enable acknowledgement, enrichment, empowerment and coexistence of multiple, even contrary, positions, and provide frameworks for participatory recordkeeping and archiving.